2015
DOI: 10.1038/srep10144
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Identification of On-Bead Peptides Using Surface-Enhanced Raman Spectroscopic Barcoding System for High-Throughput Bioanalysis

Abstract: Recently, preparation and screening of compound libraries remain one of the most challenging tasks in drug discovery, biomarker detection, and biomolecular profiling processes. So far, several distinct encoding/decoding methods such as chemical encoding, graphical encoding, and optical encoding have been reported to identify those libraries. In this paper, a simple and efficient surface-enhanced Raman spectroscopic (SERS) barcoding method using highly sensitive SERS nanoparticles (SERS ID) is presented. The 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Raman spectroscopy confirmed the selective deposition of the functionalized thiols on finger regions of the gold IDAs ( Supplementary Fig. 6), with the Raman spectra of the thiols matching literature values 42 .…”
Section: Scanning Electron Microscopy (Sem) and Focus Ion Beam (Fib)supporting
confidence: 80%
“…Raman spectroscopy confirmed the selective deposition of the functionalized thiols on finger regions of the gold IDAs ( Supplementary Fig. 6), with the Raman spectra of the thiols matching literature values 42 .…”
Section: Scanning Electron Microscopy (Sem) and Focus Ion Beam (Fib)supporting
confidence: 80%
“…SERS is a promising immunodetection technique due to its exceptional sensitivity, specificity, and multiplexing ability with minimal spectral overlap between various reporter molecules. [12][13][14][15][16] The antenna-like behavior of GNSs is attributable to their unique geometry, where their core acts as an antenna and absorbs near-infrared light and their branches behave as emitters to localize the absorbed light at the tips to generate intense electric fields. [17][18][19] We have shown that the near-field electromagnetic radiation generated at the protrusions of GNSs gives rise to a > 10 9 enhancement in SERS signal, resulting in ultrasensitive detection in vitro, in vivo, and in biosensors.…”
mentioning
confidence: 99%
“…Nowadays, multi-mode measurement is an inevitable trend in study of cells and biological tissues 32 33 . With the development of SERS technologies, easy-handling, low cost and controllability and reproducibility are important requirements for substrate production 34 35 . The gold plating technique incorporated with ZnO NRs growth can fabricate fine Au nanostructure on microelectrodes with high controllability and low-cost.…”
Section: Resultsmentioning
confidence: 99%